1994
DOI: 10.1007/bf00868256
|View full text |Cite
|
Sign up to set email alerts
|

Urinary mineral excretion among normal Taiwanese children

Abstract: Prompted by a large population of children with renal stones seen in 20 of our country's teaching hospitals over the past 10 years, this study of urinary mineral excretion in normal children was performed. Fasting urine from 1,072 normal Taiwanese school children and 24-h urine collections from 125 children separated into three age groups were analysed for calcium (Ca), phosphate, magnesium (Mg), uric acid, sodium (Na) and creatinine (Cr). Fasting Ca/Cr ratios were not different between the sexes. Ca/Cr ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
31
6
4

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 17 publications
9
31
6
4
Order By: Relevance
“…This finding was well corroborated with several previous studies [9,16,[19][20][21][22]. It also observed that for every age group, different urine Ca/Cr ratio was reported [3,8,23]. This difference may be due to exposure to sunlight, climate, genetics, nutritional habits, drinking water and ethnicity.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding was well corroborated with several previous studies [9,16,[19][20][21][22]. It also observed that for every age group, different urine Ca/Cr ratio was reported [3,8,23]. This difference may be due to exposure to sunlight, climate, genetics, nutritional habits, drinking water and ethnicity.…”
Section: Resultssupporting
confidence: 91%
“…As for most analytes, the lower and upper reference limits are assumed to demarcate the estimated 2.5 th and 97.5 th percentiles respectively, of the underlying distribution of values [24], percentile values of urinary Ca/Cr ratio were calculated. 95 th and 97.5 th percentile for urinary Ca/Cr ratio of different age groups in present study in this geographic area was the same as some reports and different with other [1,6,9,10,[14][15][18][19][20][21][22][23][25][26][27][28][29]. Then upper reference value of urinary Ca/Cr ratio of different age group were found and this to some extent different from one previous study [11].…”
Section: Resultssupporting
confidence: 60%
“…O resultado obtido para a excreção de cálcio em urina, em 24 horas, em mg/kg, comprovou o que já é consenso na comunidade científica mundial [6][7][8]24,25 . A coleta de urina em amostra única, com jejum noturno, foi utilizada por diversos autores 6,[24][25][26] .…”
Section: Discussionunclassified
“…A coleta desse tipo de amostra apresenta grandes dificuldades práticas, especialmente em pacientes pediátri-cos, podendo incorrer em erros e representar incômodo para a criança e ônus para a família. Os inconvenientes desse tipo de coleta levaram os pesquisadores a utilizarem os quocientes cálcio/creatinina [6][7][8] , ácido úrico/creatinina 6,7,9 e citrato/creatinina 10 em amostras urinárias simplificadas ou avaliar a excreção desses elementos nessas mesmas amostras, corrigida pelo clearance de creatinina ou em mg/dl do ritmo de filtração glomerular -RFG 6,11,12 .…”
Section: Introductionunclassified
“…Foram incluídos no estudo pacientes que preenchessem os critérios de diagnóstico da hipercalciúria idiopática e ausên-cia de endocrinopatias, nefropatias, outras enfermidades das vias urinárias ou doenças metabólicas que poderiam levar a hipercalcemia e/ou hipercalciúria secundárias; ausência de tratamento atual ou no passado recente (2 meses) com medicamentos contendo cálcio, vitamina D ou qualquer outra droga com ação no metabolismo do cálcio; controle esfincteriano vesical diurno e noturno; ausência de tratamento para hipercalciúria idiopática há pelo menos um ano. O diagnóstico da hipercalciúria idiopática foi baseado na excreção urinária de cálcio maior ou igual a 4mg/kg/ 24h 1,15,16 . Eram 264 pacientes do sexo masculino e 207 do sexo feminino.…”
Section: População Estudada E Métodosunclassified